2002
DOI: 10.1007/s10350-004-6419-2
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Correlation Between Objective Anal Testing, Rupture Grade, and Bowel Symptoms After Primary Repair of Obstetric Anal Sphincter Rupture?

Abstract: Anal sphincter rupture and transanal ultrasound grade correlated with each other ( rs= 0.427, P= 0.001). Both rupture and transanal ultrasound grade correlated with soiling grade ( rs= 0.2, P= 0.03 for both), but in a multiple regression analysis, only transanal ultrasound grade was significant ( P= 0.001) as an independent variable. Anal incontinence score correlated with all the manometry variables, but in a multiple regression analysis, only squeeze pressure was significant ( P= 0.001, beta = -0.4) as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
2
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
7
20
2
3
Order By: Relevance
“…In agreement with other research teams we found a high frequency of endosonographic sphincter defects after primarily sutured sphincter tears 4,8,20,25 . By using an endosonographic defect scoring system we quantified the sphincter damage and described its change over time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other research teams we found a high frequency of endosonographic sphincter defects after primarily sutured sphincter tears 4,8,20,25 . By using an endosonographic defect scoring system we quantified the sphincter damage and described its change over time.…”
Section: Discussionsupporting
confidence: 93%
“…This might be explained by difficulties with correctly classifying the tear at surgical repair and/or by lack of statistical power, there being only three fourthdegree tears in our study. Nazir and colleagues found endosonographic defects to be significantly larger in a group of women with a total third-degree tear or a fourthdegree tear than in a group with a partial third-degree tear 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that anal sphincter defects are associated with lower resting and squeeze pressure in women following OASIS [2,[14][15][16]. However, no definitive cut-off values that discriminate between an intact sphincter and the presence of an anal sphincter defect have been published.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of anal incontinence after such injury is extremely high [4] and is believed to affect millions of women worldwide [5]. Anal incontinence incorporates a range of symptoms, including flatus incontinence, passive soiling, and incontinence of solid or liquid stool, which is a social and hygienic problem [6].…”
Section: Introductionmentioning
confidence: 99%